Intensity, Duration, and Frequency of Post‐Dialysis Fatigue in Patients on Chronic Haemodialysis. Issue 2 (26th January 2020) - Bossola, Maurizio; Di Stasio, Enrico; Monteburini, Tania; Parodi, Emanuele; Ippoliti, Fabio; Bonomini, Mario; Santarelli, Stefano; Eugenio Nebiolo, Pier; Sirolli, Vittorio; Cenerelli, Stefano
SUMMARY: Background: Although frequent and debilitating, little is known about the characteristics of post‐dialysis fatigue (PDF). Objective: To characterise the intensity, duration and frequency of PDF and the associated variables in patients on chronic haemodialyses. Design: Prospective, observational and multicenter study. Patients: We studied 271 patients. Measurements: Patients were considered to be suffering from PDF if they spontaneously offered this complaint when asked the open‐ended question: "Do you feel fatigued after dialysis? Then, each patient was invited to rate the intensity, duration and frequency of PDF from 1 to 5. Results: One hundred sixty‐four patients (60.5%) had PDF. The median [95% confidence interval (CI)] scores of PDF intensity, duration and frequency were 3 (3–4), 3 (3–4) and 4 (4‐4), respectively. The median (95% CI) of the sum of the scores (Sum Score) of PDF intensity, duration and frequency was 11 (10–12). Seventy four patients had a Sum Score ≥ 12. Using multiple regression analysis, PDF intensity was associated with dialytic age and ultrafiltration rate (UFR), PDF duration with dialytic age, while PDF fatigue frequency was associated with height. The Sum Score was associated with dialytic age and recovery time and negatively associated with daily activity, height and UFR (ml/kg/h). Conclusion: The intensity, duration and frequency of PDF are high in a large percentage of patients, suggesting that PDF is an intense event in terms of quantity and quality. Understanding the relationship between the variables associated with PDF and its intensity, duration and frequency may help better understand the underlying mechanisms of this burdensome condition.